Association between free triiodothyronine and diabetic retinopathy: insights from a longitudinal cohort study and Mendelian randomization - Feng, Xiaotong; Zhao, Hongling; Xu, Yongsong; Li, Xianhua; Cao, Haodi; Wang, Yingxiang; Zhao, Dong; Ke, Jing (Frontiers in Endocrinology, 2025)
BackgroundGrowing evidence indicates that thyroid function plays a critical pathophysiological role in diabetic microvascular complications. Nevertheless, the specific association between thyroid hormones, particularly free triiodothyronine (fT3), and diabetic retinopathy (DR) remains controversial.MethodsAfter applying the inclusion and exclusion criteria, 3703 patients were included in the baseline analysis. Multivariate logistic regression models were employed to assess the cross-sectional association between baseline fT3 levels and both the prevalence of DR. Subsequently, 1476 patients who underwent follow-up fundus photography were eligible for the retrospective cohort study. This secondary analysis examined the relationship between baseline fT3 quartiles and the risk of DR onset or progression. Additionally, two-sample Mendelian randomization (MR) analysis was performed to analyze the causal effect of circulating fT3 on non-proliferative DR (NPDR) and proliferative DR (PDR).ResultsIn the cross-sectional analysis, higher fT3 levels were inversely associated with DR after multivariable adjustment, including NPDR (OR = 0.61, 95% CI: 0.50-0.74) and PDR (OR = 0.24, 95% CI: 0.13-0.44). In the longitudinal cohort, patients with moderate fT3 levels (Q2–Q3) had a lower risk of DR onset or progression versus the lowest quartile (Q1). This protective association remained significant in those with suboptimal glycemic control (HbA1c ≥7%) or longer diabetes duration (≥ 10 years), with risk reductions of 43% (Q2) and 37% (Q3) in the former, and 44% (Q2) and 49% (Q3) in the latter. Notably, among older patients (≥ 55 years), the benefit extended across Q2-Q4. Finally, the MR analysis suggested a potential protective effect of higher fT3 levels on NPDR (MR Egger, OR = 0.131, 95% CI: 0.023-0.755, P = 0.044).ConclusionIn conclusion, our study demonstrated an inverse association between fT3 levels and the risk of both NPDR and PDR. Moderate fT3 levels were associated with a lower risk of DR onset or progression, particularly among patients with suboptimal glycemic control (HbA1c ≥7%) or longer diabetes duration (≥ 10 years). In older patients (≥ 55years), even relatively higher fT3 levels may be protective. MR analysis suggested a potential protective effect of elevated fT3 levels on the risk of NPDR, which was significant only in the MR Egger model.